Delovnopravna problematika zaposlovanja in dela mladih - Tičar, Luka (Delavci in delodajalci, 2014)
The author comprehensively deals with the position of young people in the labour market, addressing both the issue of employment on the grounds of employment contract and the general situation of young people regarding work. The latter raises a number of questions on forms of work beyond employment relationship, which are categorised as formal and are yet precarious. The author takes a critical stance towards the more or less precarious, both the existing and the emerging forms of work. He illuminates the scheme Youth Guarantee and the proposal for a new law that will regulate student work from the legal perspective. In the Youth Guarantee he exposes the issue of young people who are being trained in the workplace. The author places the phenomenon of student work alongside the employment relationship, which according to his firm opinion still remains the central legal environment of work.
Keywords: delovno pravo; mladina; študenti; trg dela; trg delovne sile; zaposlovanje